Development of Feeding Cues During Infancy and Toddlerhood. Issue 4 (July 2016) - Hodges, Eric A.; Wasser, Heather M.; Colgan, Brook K.; Bentley, Margaret E.
Abstract: Purpose: To enhance responsive feeding, this study aimed to characterize the development of feeding cues during infancy and toddlerhood. Study Design and Methods: A secondary analysis was performed on a dataset of first-time, low-income African American mother–infant pairs assessed at infant age 3, 6, 9, 12, and 18 months. A subsample with the 15 highest, middle, and lowest infant body mass index (BMI) Z-scores at 18 months was selected ( n = 45). Using video-recorded home feedings, early, active, and late receptiveness and fullness cues were assessed using the Responsiveness to Child Feeding Cues Scale at each time point. Descriptive statistics were used to characterize development. Results: Early receptiveness cues were relatively rare over time, whereas active receptiveness cues were much more common. However, there were changes over time. For example, settling into the feeding decreased from ~50% at 3 and 6 months to 4.8% by 18 months, whereas postural attention and reaching for food increased after 6 months. In the first 6 months, falling asleep and decreasing muscle tone and activity level were the most common early fullness cues. Thereafter, taking interest in surroundings was most prevalent. Active fullness cues became increasingly diverse after 6 months, led by more assertive cues such as pushing or pulling away and communicating "no" verbally or nonverbally. Clinical Implications: These findings provide an empirical description of waxing and waning in feeding cues and indicate increasing intentionality of cues over the first 18 months of life. Knowing common cues across development may aid clinicians in enhancing parental feeding responsiveness, avoiding overfeeding, thereby decreasing risk of early childhood obesity. Abstract : The first two years of life are a very important period for development of obesity and its prevention. Obesity affects 8.1% of infants in the United States. Helping caregivers recognize the range of hunger and fullness cues an infant might express over the course of development is essential to responsive feeding and may be a factor in preventing overfeeding, overeating, and risk of obesity.